Phytochemical Screening and Cytotoxicity of Root Extracts of Eupatorium odoratum Against the Shrimp Nauplii of Artemia salina - Amatya, S.; Tuladhar, S. M. (Biological Sciences - PJSIR, 2005)
Extracts of roots of Eupatorium odoratum were fractionated using various organic solvents. The fractions so obtained were petroleum ether extract (F1), solid residue left after ethanol extraction (F2), liquid residue left after ethanol extraction (F3), hexane soluble sub-fraction of F2 (F2-1), dichloromethane-soluble sub-fraction of F2 (F2-2), ethyl actate- soluble sub-fraction of F2 (F2-3), and 80% aqueous methanol soluble sub-fraction of F2 (F2-4). The root extract fractions were screened for such phytochemicals as sterols, triterpenoids, polyphenols, carbohydrates and reducing sugurs, alkaloids, flavonoids, quinones, and tannins. These root extract fractions were further tested for their cytotoxicity in the brine shrimp lethality test. The LC50 values indicated that F1, F2-1 and F2-2 were significantly cytotoxic against the brine shrimp nauplii. The fractions F3, F2-3 and F2-4 showed no cytotoxicity, whereas F2 was mildly cytotoxic in the brine shrimp lethality test.